Reproduction, health, and medicine - Armstrong, Elizabeth Mitchell; Markens, Susan; Waggoner, Miranda R. (Emerald Publishing Limited, 2019)
At a moment when reproduction is increasingly politicized, this volume explores the breadth of contemporary research on reproduction from the perspective of medical sociology, illuminating the lived experience of reproduction and offering insights to inform sociology and health policy. Reproduction, Health, and Medicine elucidates the tensions and contradictions between the normal physiologic processes of pregnancy and birth and the sociocultural beliefs, values, and arrangements that shape how we experience these biological phenomena. Investigating a range of reproductive events and experiences, including pregnancy, birth, abortion and fertility planning, the volume advances our understanding of how lay people and professionals make cultural meaning out of these processes in diverse settings. The chapters highlight how studies of reproduction, health, and medicine interface with core sociological concepts such as stratification, inequality, intersectionality, family and kinship, risk, and social control, and how experiences of reproduction are shaped by gender, race, class, sexuality and citizenship, as well as culture, health care systems, and health politics.
Introduction: Reproduction through the lens of medical sociology / Susan Markens, Elizabeth Mitchell Armstrong, And Miranda R. Waggoner -- Part I. Medical technology as peril or promise -- Post-abortion care in Senegal: a promising terrain for medical sociology research on global abortion politics / Siri Suh -- When less is more: shifting risk management in American childbirth / Kellie Owens Bhutanese -- Refugees, mothering, and medicalization / Ashley F. Kim -- Women's motivations for "choosing" unassisted childbirth: a compromise of ideals and structural barriers / Lauren A. Diamond-Brown -- Part II. Knowledge and its consequences -- Reframing and resisting: how women navigate the medicalization of pregnancy weight / David J. Hutson -- Complicating the generational disconnect: pregnant women, grandmothers-to-be, and medicalization / Danielle Bessett -- A matter of health and safety: science and the state in texas abortion legislation / Alexis M. Kenney -- Stratification in reproductive healthcare: an analysis of pathways of inclusion among sexual minorities, substance users, and women who use midwives / Katharine Mccabe -- Part III. Reproductive experiences and decision-making -- The legacy of symphysiotomy in Ireland: a reproductive justice approach to obstetric violence / Cara Delay and Beth Sundstrom -- "My abortion made me a good mom": an analysis of the use of motherhood identity to dispel abortion stigma / Andréa Becker -- Feeding the cesarean cycle? Examining the role of childbirth education classes / Katherine M. Johnson, Richard M. Simon, Jessica L. Liddell, and Sarah Kington -- Family completion as part of the reproductive cycle: what it means to be "done" / Alexis T. Franzese, Kaitlin Stober, And Amy Mccurdy.
Print version record.
Keywords: Reproductive health; Women -- Health and hygiene; Health & Fitness, Women's Health; Women's health